2018
DOI: 10.1177/2233865918815008
|View full text |Cite
|
Sign up to set email alerts
|

Regionalism and presidential ideology in the current wave of Latin American integration

Abstract: Latin American regionalism is currently undergoing a profound crisis. Although the recent wave of regionalism of the early 21st century raised high expectations just a few years ago, it has suffered some important drawbacks since, as illustrated by the suspension of Venezuela from Mercosur in 2017 or the debacle of the Union of South American Nations in April 2018. Regional integration theories extrapolated from the European case struggle to account for the short cycles of integration dynamics in Latin America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…Por su parte, [6] analizan es su estudio la relación entre las ideologías de los presidentes latinoamericanos y el regionalismo en América Latina, prestando especial atención a la diplomacia presidencial y el papel de las ideas que llevan a la conformación de diversas ideologías en el regionalismo desde inicios del siglo XXI, estudiando los casos de la Alianza del Pacífico, MERCOSUR, la Comunidad Andina (CAN) y UNASUR. El estudio se basó en una encuesta de 16 preguntas, aplicada a 94 expertos en 15 países, que midió el comportamiento de los presidentes de la región en materia de política exterior y otras categorías en un espectro ideológico.…”
Section: Marco Teórico Conceptualunclassified
“…Por su parte, [6] analizan es su estudio la relación entre las ideologías de los presidentes latinoamericanos y el regionalismo en América Latina, prestando especial atención a la diplomacia presidencial y el papel de las ideas que llevan a la conformación de diversas ideologías en el regionalismo desde inicios del siglo XXI, estudiando los casos de la Alianza del Pacífico, MERCOSUR, la Comunidad Andina (CAN) y UNASUR. El estudio se basó en una encuesta de 16 preguntas, aplicada a 94 expertos en 15 países, que midió el comportamiento de los presidentes de la región en materia de política exterior y otras categorías en un espectro ideológico.…”
Section: Marco Teórico Conceptualunclassified
“…El regionalismo latinoamericano es a la vez intergubernamental e interpresidencial. Esta combinación ha impulsado la integración regional a través de una diplomacia de cumbres, especialmente en épocas de fuertes liderazgos presidenciales y afinidades políticas entre presidentes y presidentas (Álvarez, 2021;Baracaldo y Chenou, 2019;Deciancio y Quiliconi, 2022b;Quiliconi y Rivera, 2019). Sin embargo, estas características del regionalismo latinoamericano han provocado bloqueos y retrocesos en tiempos de polarización y falta de consenso político.…”
Section: El Regionalismo Latinoamericano En Crisisunclassified
“…There is a relationship between changes of governments in Latin America, especially if they also involve changes of presidential ideology, and regionalism. Baracaldo Orjuela and Chenou (2019) have shown that ideological affinity or distance between presidents directly affects the success or crisis of a regional integration organization. In this sense, the greater affinity between the presidents of Mercosur and Pacific Alliance countries regarding open regionalism, as signaled in the 2018 Presidential Declaration, and the goal of promoting extra‐regional agreements was a variable that affected the rapprochement between blocs from 2016 onward.…”
Section: Convergence In Diversity: Rapprochement Between the Pacific ...mentioning
confidence: 99%
“…The ideological imbalance in Mercosur beginning in 2016 directly affected its stability, with the friction between Argentina, Brazil, and Paraguay on the one hand, and Venezuela on the other, with the most emblematic episode resulting in the suspension of the latter from Mercosur (Baracaldo Orjuela & Chenou, 2019). Paraguay was the country that advocated openly that Mercosur's PPT situation should not generate friction with the Pacific Alliance (Exame, 2016).…”
Section: Convergence In Diversity: Rapprochement Between the Pacific ...mentioning
confidence: 99%